2015
DOI: 10.3109/10428194.2015.1072766
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood EBV-DNA predicts outcome in diffuse large B-cell lymphoma

Abstract: An association between Epstein-Barr Virus (EBV) infection and lymphoproliferative diseases has been reported with EBV + diffuse large B cell-lymphoma (DLBCL) of the elderly described as a distinct entity. In a cohort of 218 human immunodeficiency virus (HIV)-negative patients with diffuse large B-cell lymphomas, we detected EBV-DNA in 25% of whole blood (WB) samples at diagnosis. Presence and viral load in WB, mononuclear cells or plasma did not predict the presence of EBV in the tumor biopsy. Positive Hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
2
19
1
Order By: Relevance
“…Some of the same studies have also suggested that EBER+ PTCL‐NOS, defined as having at least one EBER+ cell per high power field (HPF), represent a relatively large subset (30–41%) of all cases and may have a worse outcome than EBER negative PTCL‐NOS, although the age group affected differed among studies . This would be in line with the negative prognostic impact conferred by EBV on diffuse large B‐cell lymphoma (DLBCL) and classical Hodgkin lymphoma (cHL) …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some of the same studies have also suggested that EBER+ PTCL‐NOS, defined as having at least one EBER+ cell per high power field (HPF), represent a relatively large subset (30–41%) of all cases and may have a worse outcome than EBER negative PTCL‐NOS, although the age group affected differed among studies . This would be in line with the negative prognostic impact conferred by EBV on diffuse large B‐cell lymphoma (DLBCL) and classical Hodgkin lymphoma (cHL) …”
Section: Discussionmentioning
confidence: 98%
“…conferred by EBV on diffuse large B-cell lymphoma (DLBCL) and classical Hodgkin lymphoma (cHL). 9,39 With the exception of ENKTL, where EBV uniformly infects NK cells, the lineage of the EBER1 cells in PTCL has generally been left unaddressed; mostly due to technical challenges and the poor resolution afforded by IHC-ISH double staining, especially when the number of EBER1 cells is small. However, EBER1 large, atypical T-cells have been described in PTCL, sometimes in large numbers, 2,23 suggesting that EBV can infect neoplastic T-cells; therefore, raising questions about the mechanism of viral entry (T-cells do not typically express CD21, the canonical receptor for EBV) and the potential oncogenic role of the virus in these neoplasms.…”
Section: Tumor Markers and Signaturesmentioning
confidence: 99%
“…Therefore, EBV-DNA assay using whole blood is relatively easy to detect and easy to handle [ 32 , 33 ]. Recent studies showed that EBV-DNA in whole blood was useful for predicting the clinical outcome in HL or DLBCL [ 15 , 16 ]. In relapsed/refractory ENKL, EBV-DNA in whole blood is a more sensitive marker than plasma EBV-DNA in predicting response or adverse events of SMILE (steroid, methotrexate, ifosfamide, L-asparaginase, and etoposide) chemotherapy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma sample has been used in most studies, there is still controversy regarding which blood source could reflect the disease characteristics more accurately. Some studies have reported that whole blood EBV-DNA could also be a good source for predicting outcome in HL or diffuse large B-cell lymphoma (DLBCL) [ 15 , 16 ]. Although EBV positivity in tumor tissue has been related with negative prognosis in PTCL, there are few data regarding the role of circulating EBV-DNA in PTCL [ 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the standardized incidence rates for most NADCs were greater than doubled in HIV population, and lower CD4 + T cells and taking HAART were found to be two major risk factors [33]. Moreover, it has been believed that the EBV DNA load and HIV viremia are correlated [34] and could serve as the diagnostic and prognostic marker for lymphoma in HIV-infected patients [35][36][37][38]. Based on these evidence and our finding, we suggest closer surveillance of EBV-related cancer incidence, known risk factors, as well as biomarkers including EBV DNA especially among PLWHA with lower CD4 counts or with HIV viremia.…”
Section: Discussionmentioning
confidence: 99%